PREINFARCTION ANGINA AS A CLINICAL FORM OF THE ISCHEMIC PRECONDITIONING PHENOMENON - E. A. Lykasova; V. V. Todosiychuk; V. A. Kuznetsov; Y. A. Yurkina (Кардиоваскулярная терапия и профилактика)
Brief episodes of myocardial ischemia initiate a cascade of endogenous mechanisms which protect the heart during further ischemic attack. This phenomenon is called an ischemic preconditioning. Preinfarction angina is a clinical model of this phenomenon. Clinical studies have demonstrated that preinfarction angina is associated with: lower incidence of cardiogenic shock, pulmonary edema, ventricular tachycardia and ventricular fibrillation, reduced infarct size, less severe left ventricular dysfunction, better results of thrombolytic therapy, less severe myocardial reperfusion injury, better hospital and long-term prognosis. There is evidence that elderly age, presence of diabetes mellitus, left ventricular hypertrophy and hypercholesterolemia do reduce the cardioprotective effect of preinfarction angina. Preinfarction angina may be an additional criterion of risk stratification in myocardial infarction patients. This review summarizes data from the literature on the most important aspects of preinfarction angina.